Prevalence of lung cancer in chronic obstructive pulmonary disease: A systematic review and meta-analysis - Zhao, Guixiang; Li, Xuanlin; Lei, Siyuan; Zhao, Hulei; Zhang, Hailong; Li, Jiansheng (Frontiers in Oncology, 2022)
Background: There is growing evidence that chronic obstructive pulmonary disease (COPD) can increase the risk of lung cancer, which poses a serious threat to treatment and management. Therefore, we performed a meta-analysis of lung cancer prevalence in patients with COPD with the aim of providing better prevention and management strategies. Methods: We systematically searched PubMed, EMBASE, Web of Science, and Cochrane Library databases from their inception to March 20, 2022, to collect studies on the prevalence of lung cancer in patients with COPD. We evaluated the methodological quality of the included studies using the tool for assessing the risk of bias in prevalence studies. Meta-analysis was used to determine the prevalence and risk factors for lung cancer in COPD. Subgroup and sensitivity analyses were conducted to explore the data heterogeneity. Funnel plots combined with Egger's test were used to detect the publication biases. Results:31 studies, covering 829,490 individuals were included to investigate the prevalence of lung cancer in patients with COPD. Pooled analysis demonstrated that the prevalence of lung cancer in patients with COPD was 5.08% (95%CI:4.17%-6.00%). Subgroup analysis showed that the prevalence was 5.09% (95% CI:3.48%-6.70%) in male and 2.52% (95% CI:1.57%-4.05%) in female. The prevalence of lung cancer in COPD patients who were current and former smokers was as high as 8.98% (95%CI:4.61%-13.35%) and 3.42% (95%CI:1.51%-5.32%); the incidence rates in patients with moderate and severe COPD were 6.67% (95%CI:3.20%-10.14%) and 5.57% (95%CI:1.89%-16.39%), respectively, which were higher than the 3.89% (95%CI:2.14%-7.06%) estimated in patients with mild COPD. Among the types of lung cancer, adenocarcinoma and squamous cell carcinoma were the most common, with incidence rates of 1.59% (95%CI:0.23%-2.94%) and 1.35% (95%CI:0.57%-3.23%), respectively. There were also differences in regional distribution, with the highest prevalence in the Western Pacific region at 7.78% (95% CI:5.06%-10.5%), followed by the Americas at 3.25% (95% CI:0.88%-5.61%) and Europe at 3.21% (95%CI:2.36%-4.06%). Conclusions: This meta-analysis shows that COPD have a higher risk of developing lung cancer than those without COPD. More attention should be given to this result in order to reduce the risk of lung cancer in these patients with appropriate management and prevention.